Case of pneumatosis cystoides intestinalis with intra‐abdominal free air developed during treatment with voglibose. Issue 9 (5th August 2022) - Hisanaga, Etsuko; Sano, Takaaki; Kumakura, Yuji; Yokoyama, Yozo; Nakajima, Isao; Takagi, Hitoshi
Abstract : Contrast‐enhanced computed tomography (CT) scan (portal phase) at the onset. Emphysema is detected in the ileal wall (b, c: Arrows) and free air is detected in the abdominal cavity (a: Arrowhead). CT scan imaging settings: (a–c) window level (WL) 60 and window width (WW) 300. (d–f) WL 0 and WW 433. By changing the imaging settings, intestinal emphysema and free air can be more easily identified.